Evaluation of antifungal activity of citrus grandis Essential oil and chemical composition - VISHNU SHARMA,; ANIMA SHARMA,; RUCHI SETH, (International Journal of Pharma and Bio Sciences, 2017)
The fungi have an important role in the environment. They cause the infections when grow on human. There is urgent need to get a new therapeutics or remedies from nature to inhibit the growth of pathogenic fungi. In the present study, the chemical composition of Citrus grandis volatile oil and anti-dermatophytic activity was evaluated against isolated dermatophytic species. The Clear pale yellowish color with fresh and sweet aroma oil was extracted from the leaves of Citrus grandis that revealed the presence of 39 volatile components. The oil has revealed excellent inhibition activity against test organisms with presence of Maximum Inhibition Zone of 14.33 mm for Microsporum gypsium as well as 14 mm against Trichophyton mentagrophytes (KU578106) as compared to standard. The present study detailed to chemical composition of Citrus grandis volatile oil with the confirmative presence of phenol components. The data also prove the anti-dermatophytic potential against Microsporum and Trichophyton species. The data also represent the further requirements for to investigate the various pharmacological behaviors to its commercialization for the advantage of human beings.